Coping strategies and support provided by educational centres to teenage mothers re-engaging with education post-pregnancy: a case study of a township school in South Africa - Malatji, Hlologelo; Dube, Nkosiyazi; Nkala-Dlamini, Busisiwe; Shumba, Kemist (Penerbit Universiti Kebangsaan Malaysia, 2023)
Teenage girls who conceive while in school are often confronted with a number of health, social and economic hardships. As a result of the pregnancy related hardships, some of the teenagers drop out of school and fail to re-enter the school system after giving birth. However, a growing body of literature show some of these teenagers re-enter the school system after giving birth to continue with their studies. We employed a qualitative approach to explore the coping strategies by teenage mothers when they returned to school following childbirth and the support mechanisms used by the schooling system to meet their learning needs. We adopted a single case study design of a South African township school in Gauteng Province, South Africa. We collected data using in-depth one-on-one interviews involving teenage mothers. The findings revealed that consultations with educators and participation in after-school programs, with the aim of catching-up on missed content was some of the coping strategies used by teenage mothers re-engaging with education following childbirth. In addition, sympathetic educators provided extra consultation time slots and also motivated the teenagers to persevere and focus on their studies. A call is made for schools to enhance learner support programs, especially those aimed at supporting teenage mothers who decide to return to school to complete their studies after giving birth.